1981
DOI: 10.1007/bf00278860
|View full text |Cite
|
Sign up to set email alerts
|

Red cell antigen, serum protein, and red cell enzyme polymorphisms in inhabitants of the Jimi Valley, Western Highlands, New Guinea

Abstract: A series of blood samples from four villages in the Jimi Valley, Western New Guinea Highlands, has been tested for genetic variation in blood group, serum protein, and red cell enzyme systems. Polymorphic variation was present for the AB0, MNS, P, and Rh blood group systems, for the Hp and Tf serum protein systems, and for the acid phosphatase, 6-PGD, PGM, MDH, and ADA enzyme systems. One each of the following variants was detected: Ge(a-), G6PD deficient, AK 2-1 and PHI 7-1 or 8-1. All samples tested were Cw-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Why has P. falciparum evolved so many pathways for invasion? The erythrocyte surface molecules are highly polymorphic within the human population (34)(35)(36)(37)(38). It has been reported that the fastest evolving genes in the human lineage are the glycophorins A and B (39).…”
Section: Discussionmentioning
confidence: 99%
“…Why has P. falciparum evolved so many pathways for invasion? The erythrocyte surface molecules are highly polymorphic within the human population (34)(35)(36)(37)(38). It has been reported that the fastest evolving genes in the human lineage are the glycophorins A and B (39).…”
Section: Discussionmentioning
confidence: 99%